Comparison of cognitive and neuropsychiatric profiles in hospitalised elderly medical patients with delirium, dementia and comorbid delirium–dementia. Issue 3 (8th March 2016) - Leonard, Maeve; McInerney, Shane; McFarland, John; Condon, Candice; Awan, Fahad; O'Connor, Margaret; Reynolds, Paul; Meaney, Anna Maria; Adamis, Dimitrios; Dunne, Colum; Cullen, Walter; Trzepacz, Paula T; et al.
Abstract : Objectives: Differentiation of delirium and dementia is a key diagnostic challenge but there has been limited study of features that distinguish these conditions. We examined neuropsychiatric and neuropsychological symptoms in elderly medical inpatients to identify features that distinguish major neurocognitive disorders. Setting: University teaching hospital in Ireland. Participants and measures: 176 consecutive elderly medical inpatients (mean age 80.6±7.0 years (range 60–96); 85 males (48%)) referred to a psychiatry for later life consultation-liaison service with Diagnostic and Statistical Manual of Mental Disorders (DSM) IV delirium, dementia, comorbid delirium–dementia and cognitively intact controls. Participants were assessed cross-sectionally with comparison of scores (including individual items) for the Revised Delirium Rating Scale (DRS-R98), Cognitive Test for Delirium (CTD) and Neuropsychiatric Inventory (NPI-Q). Results: The frequency of neurocognitive diagnoses was delirium (n=50), dementia (n=32), comorbid delirium–dementia (n=62) and cognitively intact patients (n=32). Both delirium and comorbid delirium–dementia groups scored higher than the dementia group for DRS-R98 and CTD total scores, but all three neurocognitively impaired groups scored similarly in respect of total NPI-Q scores. For individual DRS-R98 items, delirium groups were distinguished from dementia groups by a range of non-cognitive symptoms, but only for impaired attention of the cognitive items. For the CTD, attention (p=0.002) and vigilance (p=0.01) distinguished between delirium and dementia. No individual CTD item distinguished between comorbid delirium–dementia and delirium. For the NPI-Q, there were no differences between the three neurocognitively impaired groups for any individual item severity. Conclusions: The neurocognitive profile of delirium is similar with or without comorbid dementia and differs from dementia without delirium. Simple tests of attention and vigilance can help to distinguish between delirium and other presentations. The NPI-Q does not readily distinguish between neuropsychiatric disturbances in delirium versus dementia. Cases of suspected behavioural and psychological symptoms of dementia should be carefully assessed for possible delirium.